Matured Tolerogenic Dendritic Cells Effectively Inhibit Autoantigen Specific CD4+ T Cells in a Murine Arthritis Model - Jansen, Manon A. A.; Spiering, Rachel; Ludwig, Irene S.; van Eden, Willem; Hilkens, Catharien M. U.; Broere, Femke (Frontiers in Immunology, 2019)
Tolerogenic dendritic cells (tolDCs) are a promising treatment modality for diseases caused by a breach in immune tolerance, such as rheumatoid arthritis. Current medication for these diseases is directed towards symptom suppression but no real cure is available yet. TolDC-based therapy aims to restore immune tolerance in an antigen-specific manner. Here we used a mouse model to address two major questions: i) is a maturation stimulus needed for tolDC function in vitro and in vivo and is maturation required for functioning in experimental arthritis and ii) can tolDCs modulate CD4+ T cell responses? To answer these questions, we compared matured and immature dexamethasone/vitamin D3-generated tolDCs in vitro. Subsequently, we co-transferred these tolDCs with naïve or effector CD4+ T cells to study the characteristics of transferred T cells after three days with flow cytometry and Luminex multiplex assays. In addition, we tested the suppressive capabilities of tolDCs in an experimental arthritis model. We found that tolDCs cannot only modulate naïve CD4+ T cell responses as shown by fewer proliferated and activated CD4+ T cells in vivo, but also effector CD4+ T cells. In addition, Treg expansions were seen in the proliferating cell population in the presence of tolDCs. Furthermore, we show that administered tolDCs are capable to inhibit arthritis in the proteoglycan-induced arthritis model. However, a maturation stimulus is needed for tolDCs to manifest this tolerizing function in an inflammatory environment. Our data will be instrumental for optimization of future tolDC therapies for autoimmune diseases.